1993
DOI: 10.1093/clinchem/39.8.1717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hemoglobin variants and derivatives on glycohemoglobin determinations, as investigated by 102 laboratories using 16 methods

Abstract: Influences of hemoglobin (Hb) variants (HbSS, HbCC, beta-thalassemia, HbAE, HbAS, HbAC, hereditary persistent HbF) and Hb derivatives (carbamylated- and acetylated-Hbs, Schiff base, and those formed in stored blood) on results of glyco-Hb assays by 102 laboratories using 16 different methods were investigated. Affinity chromatography shows deviating results only with homozygous Hb S and C. Correct interpretation of results from patients with decreased erythrocyte half-lives requires previous knowledge on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Clinical laboratory diagnosis is an essential precursor to therapeutic intervention in most diseases. In this context, it is important to exclude interference by other conditions that may give false‐positive or negative results, leading to inappropriate management (Weykamp et al, 1993; The Thalassemia Working Party of the BCSH General Haematology Task Force., 1994). Estimation of haemoglobin subtypes is important for the diagnosis of certain clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical laboratory diagnosis is an essential precursor to therapeutic intervention in most diseases. In this context, it is important to exclude interference by other conditions that may give false‐positive or negative results, leading to inappropriate management (Weykamp et al, 1993; The Thalassemia Working Party of the BCSH General Haematology Task Force., 1994). Estimation of haemoglobin subtypes is important for the diagnosis of certain clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical laboratories, haemoglobin subtypes are reported as percentages of total haemoglobin. In iron deficiency, the decreased concentration of total haemoglobin may influence the percentages of different haemoglobin subtypes (Weatherall, 1983; Nathan & Oski, 1993; Weykamp et al ., 1993; The Thalassemia Working Party of the BCSH General Haematology Task Force., 1994). Iron deficiency is thus a potential source of diagnostic interference in these tests.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, a recent study found neither a significant increase in donor erythrocyte (RBC) glycated haemoglobin (HbA1c) nor an effect on transfusion recipients (Spencer et al , 2011). We hypothesized that the discrepancy is related to the pre‐analytical physical and chemical conditions under which glycation occurs rather than to differences in specificity of the analytical methods for HbA1c (Weykamp et al , 1993). Therefore, we studied HbA1c in donor RBC in preservative solutions containing different glucose concentrations, after various 4 °C storage intervals and after RBC incubation at 20 and 37 °C.…”
Section: Effect Of Blood Sample Incubation Temperature On Glycation Omentioning
confidence: 99%
“…Physicians need to be aware that some medical conditions, such as disorders of haemoglobin metabolism, need to be taken into account when assessing HbA 1c levels 30, 31. For example, haemoglobin variants such as high levels of fetal haemoglobin (HbF) may interfere with standard assays for HbA 1c , leading to false estimates of HbA 1c concentrations 32.…”
Section: Setting and Assessing Goalsmentioning
confidence: 99%